2021
DOI: 10.1027/1618-3169/a000530
|View full text |Cite
|
Sign up to set email alerts
|

Is There Semantic Conflict in the Stroop Task?

Abstract: Abstract. This research addressed current controversies concerning the contribution of semantic conflict to the Stroop interference effect and its reduction by a single-letter coloring and cueing procedure. On the first issue, it provides, for the first time, unambiguous evidence for a contribution of semantic conflict to the (overall) Stroop interference effect. The reported data remained inconclusive on the second issue, despite being collected in a considerable sample and analyzed with both classical (frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Whereas no effects were found using a color-word Stroop task (Larson et al, 2009(Larson et al, , 2012 or an auditory Stroop task (Donohue et al, 2012), studies using a counting Stroop task or a confound-minimized prime-probe task using arrows (Larson et al, 2016) found that the N450 was modulated by previous conflict. Interference in the Stroop task can be attributed to semantic conflict as the color of the presented color-word stimulus interferes with the semantic meaning of the color-word (see, e.g., Burca et al, 2021;De Houwer, 2003;van Veen & Carter, 2005), and a similar reasoning can be applied to other Stroop-like paradigms (Kałamała et al, 2020). Retrieval conflict elicited during our WM task can also be seen as a form of semantic conflict, which would explain why conflict and post-conflict adaptation modulated the N450 in our task.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas no effects were found using a color-word Stroop task (Larson et al, 2009(Larson et al, , 2012 or an auditory Stroop task (Donohue et al, 2012), studies using a counting Stroop task or a confound-minimized prime-probe task using arrows (Larson et al, 2016) found that the N450 was modulated by previous conflict. Interference in the Stroop task can be attributed to semantic conflict as the color of the presented color-word stimulus interferes with the semantic meaning of the color-word (see, e.g., Burca et al, 2021;De Houwer, 2003;van Veen & Carter, 2005), and a similar reasoning can be applied to other Stroop-like paradigms (Kałamała et al, 2020). Retrieval conflict elicited during our WM task can also be seen as a form of semantic conflict, which would explain why conflict and post-conflict adaptation modulated the N450 in our task.…”
Section: Discussionmentioning
confidence: 99%
“…This is also true for the semantic Stroop task variant using colour-related words, although this claim is more controversial (see Besner & Young, 2024;Labuschagne & Besner, 2015;Kahan et al, 2006;Manwell et al, 2004vs. Augustinova & Ferrand, 2014Burca et al, 2021). The need for spatial attention has also been well documented in tasks other than Stroop (e.g., lexical decision and reading aloud; e.g., see INTENTION AND WORD IDENTIFICATION Lachter et al, 2004;McCann et al, 1992).…”
Section: Stroopmentioning
confidence: 97%
“…This account is prevalent in introductory psychology textbooks, cognitive psychology textbooks, chapters, and literally hundreds of refereed journal articles (e.g., see Augustinova & Ferrand, 2012a, 2014; Brown et al, 2002; Burca et al, 2021). Indeed, a brief survey of nine cognition textbooks taken more or less at random from our bookshelves revealed that “the” Stroop effect is consistently taken to indicate that word identification occurs in the absence of any intention on the part of the reader; indeed, that it cannot be prevented from occurring.…”
Section: Intention and The Concept Of Task Setmentioning
confidence: 99%
See 2 more Smart Citations